Identifikasi struktur geologi bawah permukaan berdasarkan pemodelan 3D data gravitasi (studi kasus daerah potensi panas bumi Kepahiang) - Sukmaji Anom Raharjo; Aditya Verry Saputra; Tony Rahadinata (Universitas Jenderal Soedirman, 2022)
A survey of the gravity method in the Kepahiang geothermal potential area has been carried out, covering an area of ​​12×16 km2 with a total of 332 measurement data points. This study aims to identify the subsurface geological structure and the distribution of subsurface rock density associated with the hydrothermal system of the potential geothermal area. Modeling and identifying subsurface geological structures using derivative analysis can determine the type of fault structure produced by subsurface mass's vertical contact. The 3D modeling results show a block with a low-density value located in the hot spring area in a southwest direction. The low rock density is about 2.4 g/cm3 and is interpreted as pyroclastic rock undergoing weathering due to rising hydrothermal solutions. The modeling results also show a block of rock with high density, interpreted as a response to andesite rock, basalt, which is still compact and possible as a heat source for the Kepahiang geothermal area.